Genetic insights into across pancreatitis types: the causal influence of immunoglobulin G N-glycosylation variants on disease risk - Chen, Yulin; Li, Xue; Lu, Ran; Lv, Yinchun; Ye, Junman; Huang, Qiaorong; Meng, Wentong; Long, Feiwu; Burman, Jonas; Mo, Xianming; Fan, Chuanwen (Frontiers in Immunology, 2024)
Background: While a few case-control studies indicated a possible correlation of IgG Nglycosylation patterns with pancreatitis, their restricted sample sizes and methodologies prevented conclusive insights into causality or distinguishing traits across pancreatitis types.We conducted a two-sample Mendelian Randomization (MR) analysis to investigate the causal relationship between 77 IgG N-glycosylation traits and various types of pancreatitis, including acute pancreatitis (AP), chronic pancreatitis (CP), alcohol acute pancreatitis (AAP), and alcohol chronic pancreatitis (ACP). This analysis utilized summary-level data from genome-wide association studies (GWAS), employing methods such as IVW, MR-Egger, and weighted median. To ensure the robustness of our findings, several sensitivity analyses, including Cochran's Q statistic, leave-one-out, MR-Egger intercept, and MR-PRESSO global test were conducted.Result: Our study uncovered the causal relationship between specific IgG N-glycosylation traits and various types of pancreatitis. Notably, an increase in genetically predicted IGP7 levels was associated with a decreased risk of developing AP. For CP, our data suggested a protective effect associated with higher levels of both IGP7 and IGP31, contrasting with increased levels of IGP27 and IGP65, which were linked to a heightened risk. Moreover, in the case of AAP, elevated IGP31 levels were causatively associated with a lower incidence, while higher IGP26 levels correlated with an increased risk for ACP.This study establishes causal relationship between specific IgG N-glycosylation patterns and varying risks of different pancreatitis forms, underscoring their potential as predictive biomarkers. These findings necessitate further exploration into the underlying mechanisms, promising to inform more personalized diagnostic and therapeutic strategies in pancreatitis management.